Shunt Dependence after Intraventricular Hemorrhage and Intraventricular Fibrinolysis with uPA versus rt-PA - Covrig, Raul-Ciprian; Schellinger, Peter D.; Glahn, Joerg; Alomari, Ali; Schmieder, Kirsten; Wiese, M.; Knappe, Ulrich Johannes (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2022)
Background We compare the effect of urokinase (urokinase-type plasminogen activator [uPA]) versus alteplase (recombinant tissue plasminogen activator [rt-PA]) for intraventricular fibrinolysis (IVF) in patients with intraventricular hemorrhage (IVH) on ventriculoperitoneal shunt (VPS) dependence, functional outcome, and complications in the management of IVH.Methods We retrospectively reviewed the patients admitted with IVH or intracerebral hemorrhage (ICH) with IVH within 7 years in three different departments and found 102 patients who met the inclusion criteria. The primary end points were VPS dependence and Glasgow outcome score (GOS) at 3 months. Secondary end points were rate of rebleeding under IVF and incidence of treatment-related complications. Patients were divided into three groups: group I comprised patients treated with external ventricular drain (EVD) and IVF with uPA; group II comprised patients treated with EVD and IVF with rt-PA; and group III comprised patients treated with EVD alone.Results In all, 9.8% patients needed VPS: 12.2% in group I and 15.0% in group II, with no statistically significant difference. VPS patients had higher values of the modified Graeb score (mGS), IVH score, and IVH volume. We saw a trend for a better outcome in group II, with six patients achieving a GOS of 4 or 5 after 3 months. The mortality rate was higher in groups I and III. We found no statistical difference in the complication rate between groups I and II. Logistic regression analysis revealed that higher mGS and age predicted worse prognosis concerning mortality. The risk for death rose by 7.8% for each year of age. Any additional mGS point increased the chances of death by 9.7%.Conclusion Our data suggest that both uPA and rt-PA are safe and comparable regarding incidence of communicating hydrocephalus, and age and mGS are predictive for mortality.
Keywords: intraventricular fibrinolysis; shunt dependence; uPA; rt-PA; intraventricular hemorrhage